2023
DOI: 10.1093/wbro/lkad005
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Private Schools, School Chains and PPPs in Developing Countries

Abstract: The private school sector has expanded with almost no public intervention to educate half of primary school children in many urban centers in Africa and Asia. Simple comparisons of test scores would suggest that these private schools may provide better quality than public schools, but how much of this difference is due to selection effects is unclear. Much donor and policymaker attention has proceeded on the basis that private schools do perform better, and focused on models of public subsidy to expand access,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…While private schools appeared to outrank public schools in teaching, they fared no better in most other areas, including regulatory oversight, administration and cost, test scores, and class and gender equity. Crawfurd and Hares (2021), who performed their own review of studies since Day Ashley et al's was originally published, in 2014, concluded: "There is now considerable evidence that the average effectiveness of private schools is not substantially higher than that of public schools" (ibid. : 22).…”
Section: Primary Concerns: Addressing Claims Of Equity and Quality In...mentioning
confidence: 99%
See 4 more Smart Citations
“…While private schools appeared to outrank public schools in teaching, they fared no better in most other areas, including regulatory oversight, administration and cost, test scores, and class and gender equity. Crawfurd and Hares (2021), who performed their own review of studies since Day Ashley et al's was originally published, in 2014, concluded: "There is now considerable evidence that the average effectiveness of private schools is not substantially higher than that of public schools" (ibid. : 22).…”
Section: Primary Concerns: Addressing Claims Of Equity and Quality In...mentioning
confidence: 99%
“…Additionally, private school teachers are often not as well trained as their peers in government systems, while their teaching strategies, which can include rote memorization, drilling, and other unimaginative tasks, are as or less effective than what prevails in public schools (Nambissan, 2012). The situation is unsustainable, it would seem, based on a growing number of strike actions across the Global South and the choice of some teachers to leave the profession altogether (Bold et al, 2013;Crawfurd & Hares, 2021;Srivastava, 2010).…”
Section: Primary Concerns: Addressing Claims Of Equity and Quality In...mentioning
confidence: 99%
See 3 more Smart Citations